THE INFLUENCE OF CERTIFICATION PROGRAM ON TEACHER PERFORMANCE AT THE YAYASAN DARUL FALAH PAJARAKAN PROBOLINGGO - Badrul Kafi (MANAGERE : Indonesian Journal of Educational Management, 2020)
The implementation of teacher certification is expected to have an impact on improving the quality of learning and the quality of education on an ongoing basis. But the fact that often happens that the certification allowance often does not work with the initial goal for improving teacher performance. If you carefully examine the Law of the Republic of Indonesia Number 14 Year 2005 regarding teachers and lecturers, it will be seen that the law contains an increase in the welfare of teaching staff which is characterized by functional benefits, special allowances, and professional teaching allowances. Thus, this study aims to describe the performance of certified and uncertified teachers and find out whether there is a difference in the performance of certified teachers and uncertified teachers at the Yayasan Darul Falah Pajarakan Probolinggo. The results of research was found that; (1) the performance of teachers in the Darul Falah Pajarakan Probolinggo foundation is classified as good with a high categorization of 11.7%, a high of 82.3%, and a moderate of 5.8%, and (2) There is a difference between the performance of certified teachers with the performance of teachers who are not certified in the foundation fostered by Darul Falah Pajarakan Probolinggo as proven by the calculated F value of 13,147 with a significance value of 0.001 is 0.05.